SEMEN QUALITY CHARACTERISTICS OF PEARL GUINEA FOWLS RAISED UNDER CAGE SYSTEM - G.H. Hudson; A.V. Omprakash; K. Premavalli (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The low fertility percentage is one of the major constraints for the commercial exploitation of Guinea fowl. Semen quality is one of the major determinants of fertility. Therefore, the study was carried out to screen the seminal parameters of pearl Guinea fowls as a way to analyze the possibility of artificial insemination in the above species. Twenty two male Guinea fowls were initially caged and trained for semen collection by abdominal massage technique. Semen was collected and the seminal parameters like semen volume, colour, consistency, pH, spermatozoa concentration (106/ml), spermatozoa motility (%), live spermatozoa (%) and abnormal spermatozoa (%) from individual birds were studied. Further, pooled semen from superior males selected based on the above seminal parameters were also analyzed. Based on the results it is recommended that culling of males with poor seminal attributes may have a positive impact on fertility either through artificial insemination or by natural mating thus paving way for faster genetic improvement in Guinea fowls.